Fostering solidarity for gender/ethnic reincorporation: the experience of female indigenous ex-combatants in tierra grata, cesar (2020)
This investigation was developed during the first stage of the implementation of the peace accords in the Transit Normalization Hamlet Zone (TNHZ) of Tierra Grata, Cesar, Colombia in 2017. Through interviews, discussions and ethnographic observation, we reconstructed the trajectories of two indigenous women who contributed to the ethnic reincorporation of female Fuerza Autónoma Revolucionaria del Común (FARC) ex-combatants on a micro-local level. Most ex-combatants are entangled in strong patriarchal ties and have encountered myriad difficulties on their path towards reincorporation. This work seeks to answer the following questions: Who are the main actors of the local reincorporation process? What are their personal trajectories? What are indigenous women’s main difficulties with reincorporation from an ethnic and gender perspective in Tierra Grata?. © 2018, © 2018 Informa UK Limited, trading as Taylor and Francis Group.